Research and performance evaluation on an HA integrated acid system for sandstone acidizing - Liqiang Zhao; Yiyong Pan; Yigang Liu; Xianghai Meng; Yujie Guo; Pingli Liu (Natural Gas Industry B, 2018)
When the conventional sandstone acidizing technologies are adopted, many slugs are needed in the injection of prepad fluid, treatment fluid and postpad fluid, and consequently the production and operation suffers inconveniences and difficulties. In view of this, a kind of HA integrated acid system which is mainly composed of organic polybasic acids (HA)+HCl + HF and an efficient organic solvent was developed in this paper based on the idea of integrated acid replacing ''multiple steps'' and high efficiency and intensification. Via this HA integrated acid system, the complicated blockage in sandstone reservoirs can be removed effectively. Then, experiments were carried out on this system to evaluate its performance in terms of its retardance, organic blockage dissolution, chelating and precipitation inhibition. It is indicated that this new system can not only realize the acidizing of conventional integrated acid, but also present a good retarding performance by controlling H+ multi-stage ionization step by step and by forming silica acid-aluminum phosphonate film on the surface of clay minerals; that via this new HA integrated acid system, the organic blockage can be removed efficiently; and that it is wider in pH solution range than conventional APCs (aminopolycarboxyliates) chelants, stronger in chelating capacity of Ca2+, Mg2+ and Fe3+ than conventional chelants (e.g. EDTA, NTA and DTPA), and better in precipitation inhibition on metal fluoride, fluosilicic acid alkali metal, fluoaluminic acid alkali metal and hydroxide than multi-hydrogen acid, fluoboric acid and mud acid systems. These research results provide a technical support for the plugging removal in high-temperature deep oil and gas reservoirs. Keywords: Organic polybasic acid, Integrated acid, Retardance, Chelating, Precipitation, Acidizing, Sandstone, Reservoir